Shear viscosity due to Landau damping from the quark-pion interaction - Ghosh, Sabyasachi [UNESP]; Lahiri, Anirban; Majumder, Sarbani; Ray, Rajarshi; Ghosh, Sanjay K. (Amer Physical Soc, 2013)
We have calculated the shear viscosity coefficient eta of the strongly interacting matter in the relaxation time approximation, where a quasiparticle description of quarks with their dynamical masses is considered from the Nambu-Jona-Lasinio model. Due to the thermodynamic scattering of quarks with pseudoscalar-type condensate (i.e., pion), a nonzero Landau damping will be acquired by the propagating quarks. This Landau damping may be obtained from the Landau cut contribution of the in-medium self-energy of a quark-pion loop, which is evaluated in the framework of real-time thermal field theory.